Impact of Endurance Exercises on Knocked Knees as a General Health Concern: Impact of Endurance Exercises on Knocked Knees - Munzer, Muhammad; Khan, Alamgir; Jamil, Muhammad; Iqbal Butt, Muhammad Zafar; Soomro, Javed Ali; Basit, Abdul; Inamullah, .; Ahmad, Adnan (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Knocked knees are a problem in children and adults, making it challenging to walk or run and causing knee pain. In this problem, the knees gradient inward while the ankles remain spaced apart. Objective: To analyse the impact of endurance exercises on knocked knees as a general health concern. Methods: The study participants were randomly selected from the department of sports science and physical education, University of Punjab, Pakistan. Subjects were categorized as a control group (CG) and an experiential group (EG). Each group was comprised of twenty subjects. All the subjects were informed about the risk and benefits of participation in the study. Thus, written informed consent was taken from each subject. In addition, Ethical approval (293/SPS) was also obtained from the University of the Punjab, Lahore, Pakistan. Results: The mean and standard deviation during the pre-test were 50.60±2.35, and the mean and standard deviation during the post-test was 53.05±2.33. The t value was 1.788, and Sig was .96. Therefore, the table shows no significant difference in CG in knee-knocking before and after training sessions imposed upon EG. The mean and standard deviation of EG during the pre-test was 50.00±2.07, and the mean and standard deviation of EG during the post-test was 58.35±2.20. The t value was 17.376, and Sig was .000. Therefore, there was a significant difference during pre- and post-test EG analysis in knee-knocking. Conclusion: Based on the analysis, the researcher concluded that exercise has a vital role in rehabilitating the knocked knee.